Enhancement of Web security through the design and implementation of gesture-based CAPTCHA challenge - Dayanand, Dayanand; Jeberson, Wilson (International Journal of Computer Sciences and Engineering, 2025)
In the rapidly evolving landscape of cybersecurity, safeguarding web applications against malicious attacks remains a top priority. While traditional text-based CAPTCHA mechanisms provide some level of security, they are vulnerable to automated bots and sophisticated attacks. Addressing these challenges, this research paper proposes an innovative approach to bolster web security through the design and implementation of a gesture-based CAPTCHA challenge. By harnessing the intuitive nature of human gestures, this novel CAPTCHA solution aims to offer robust protection against automated threats while ensuring a smooth user experience. The paper delineates the design principles, implementation specifics, and evaluation criteria for the gesture-based CAPTCHA challenge, underscoring its effectiveness in thwarting attacks and improving overall web security. Through empirical studies and real-world testing, the paper showcases the efficacy and user-friendliness of the proposed solution, highlighting its potential to significantly enhance the security posture of web applications. Furthermore, the paper explores the implications of integrating gesturebased CAPTCHA challenges into existing web authentication frameworks and identifies avenues for future research in this domain. In sum, this research contributes to ongoing efforts to strengthen web security amidst evolving cyber threats, providing a promising avenue for mitigating unauthorized access and malicious activities on the internet